2023
DOI: 10.19103/as.2022.0110.14
|View full text |Cite
|
Sign up to set email alerts
|

Advances in managing organic matter in turfgrass ecosystems

Abstract: Organic matter (OM) management is a critical component in sustainable turfgrass management. Organic matter improves the soils’ ability to hold nutrients and water. However, when OM accumulation is excessive, several detrimental effects develop. Turfgrass is a tillering plant, producing a considerable amount of lateral growth, which will cause inordinate OM accumulation. The objectives of this chapter are to outline how OM effects turfgrass, the available methods for monitoring and measuring OM accumulation, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Turfgrass thatch is a porous layer with stems and roots that also harbors macro- and micro-organisms [ 62 , 63 ] and is therefore expected to have a high respiration rate. Although the effects of turfgrass thatch on carbon sequestration are not fully understood, Raturi et al [ 47 ] suggested significant differences in microbial biomass carbon between thatch and the soil underneath.…”
Section: Turfgrass Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Turfgrass thatch is a porous layer with stems and roots that also harbors macro- and micro-organisms [ 62 , 63 ] and is therefore expected to have a high respiration rate. Although the effects of turfgrass thatch on carbon sequestration are not fully understood, Raturi et al [ 47 ] suggested significant differences in microbial biomass carbon between thatch and the soil underneath.…”
Section: Turfgrass Systemsmentioning
confidence: 99%
“…In addition to removal of clippings by mowing, cultivation, including verticutting to remove grass tissues and hollow-tine aerification to physically remove plant materials and organic matter, is likely to reduce the carbon pool in turfgrass systems. Other practices, such as solid-tine aerification and topdressing, add sand to the soil profile without removing organic matter and plant material [ 62 ]. Such practices dilute the organic matter in the root zone profile to promote better growth of turfgrass and are therefore unlikely to reduce the productivity of turfgrasses.…”
Section: Turfgrass Systemsmentioning
confidence: 99%